Mechanical properties and microstructure of Yb2SiO5 environmental barrier coatings under isothermal heat treatment. Issue 7 (July 2020) - Jang, Byung-Koog; Nagashima, Nobuo; Kim, Seongwon; Oh, Yoon-Suk; Lee, Sung-Min; Kim, Hyung-Tae
Abstract: Yb2 SiO5 (ytterbium monosilicate) top coatings and Si bond coat layer were deposited by air plasma spray method as a protection layer on SiC substrates for environmental barrier coatings (EBCs) application. The Yb2 SiO5 -coated specimens were subjected to isothermal heat treatment at 1400 °C on air for 0, 1, 10, and 50 h. The Yb2 SiO5 phase of the top coat layer reacted with Si from the bonding layer and O2 from atmosphere formed to the Yb2 Si2 O7 phase upon heat treatment at 1400 °C. The oxygen penetrated into the cracks to form SiO2 phase of thermally grown oxide (TGO) in the bond coat and the interface of specimens during heat treatment. Horizontal cracks were also observed, due to a mismatch of the coefficient of thermal expansion (CTE) between the top coat and bond coat. The isothermal heat treatment improves the hardness and elastic modulus of Yb2 SiO5 coatings; however, these properties in the Si bond coat were a little bit decreased.